(untitled) ("Journal "U". Economy. Management. Finance.", 2019)
The article deals with the problems associated with the lack of clarity in the understanding of the mechanisms of application of the Federal law of 07.08.2001 № 115-FZ "On combating legalization (laundering) of proceeds from crime and financing of terrorism." The paper reveals the essence of the legalization (laundering) of criminal proceeds; considers the historical background to counter this process, studied the legislative framework used both at the Russian and international levels. The analysis of the banking sector and Rosfinmonitoring in countering the legalization of income in Russia and identified the problem of violation of the rights and legitimate interests of citizens in the application of this legislation. The mechanism of the solution of the revealed problem in the future is offered.